Influence of Processing Methods on Proximate Composition and Dieting of Two Amaranthus Species from West Cameroon - Arnaud Landry Suffo Kamela; Raymond Simplice Mouokeu; Rawson Ashish; Ghislain Maffo Tazoho; Lamye Glory Moh; Etienne Pamo Tedonkeng; Jules-Roger Kuiate (International Journal of Food Science)
The effects of various processing methods on the proximate composition and dieting of Amaranthus hybridus and Amaranthus cruentus from West Cameroon were investigated in this study. Both amaranths leaves were subjected to same treatments (sun-dried and unsliced, sliced and cooked), milled, and analysed for their mineral and proximate composition. Thirty-Six Wistar albino rats of 21 to 24 days old were distributed in six groups and fed for 14 days with 10% protein based diets named D0 (protein-free diet), DI (egg white as reference protein), DII (sun-dried and unsliced A. hybridus), DIII (cooked and sliced A. hybridus), DIV (sun-dried and unsliced A. cruentus), and DV (cooked and sliced A. cruentus). The protein bioavailability and haematological and biochemical parameters were assessed in rats. The results showed that K, P, Mg, Zn, and Fe had the higher content in both samples regardless of processing method. The sun-dried and unsliced A. cruentus contained the highest value of crude protein 32.22 g/100 g DM (dry matter) while the highest crude lipid, 3.80 and 2.58%, was observed, respectively, in sun-dried and unsliced A. hybridus and cooked and sliced A. cruentus. Cooked and sliced A. hybridus and A. cruentus contained high crude fiber of 14 and 12.18%, respectively. Rats fed with diet DIII revealed the best protein bioavailability and haematological parameters whereas 100% mortality rate was recorded with group fed with diet DIV. From this study, it is evident that cooked and sliced A. hybridus and A. cruentus could play a role in weight reduction regimes.